Jenis-Jenis Basidiomycetes di Kawasan Air Terjun Sando Kota Lubuklinggau - Sepriyaningsih; Nopa Nopiyanti (Jurnal Biosilampari : Jurnal Biologi, 2024)
The aim of this research is to determine the types of basidiomycetes in the Sando Waterfall Area, Lubuklinggau City. This type of research is qualitative descriptive research. The research was conducted from September to December 2023 at Sando Waterfall, West Lubuklinggau I District, Lubuklinggau City. The method used in this research is a direct survey in the field by exploring the Sando Waterfall area. Data collection have made a brief description of the species and the habitat in which they were found. Species found are photographed to the identification process and data analysis used in this research is descriptive qualitative. The species found were identified using guidebooks about mushrooms, mushroom identification websites, and journals about mushrooms. Based on the research results, 18 species of macroscopic fungi were found, i.e. Tremidis sp., Polyporus squamosus, Ganoderma lucidum, Trametes lactinea, Armillaria mellea, Ganoderma applanatum, Ceriporus squamosus, Oudemansiella mucida, Microporus xanthopus, Galiella rufa, Trametes ochracea, Trametes gibbosa, Lentinus crinitus, Schizophyllum commune, Auricularia auricula, Phycnosporus sanguineus, Coprinus plicatilis, and Hexagonia tenuis. The habitat of these fungi is most often found in plant litter.